LEGAL CONSEQUENCES FOR DEVELOPERS WHO MAKE GAMES CONTAINING ADULT CONTENT IN INDONESIA - Bagus Gede Ari Rama (Fakultas Hukum Universitas Dwijendra, 2024)
This study explores the legal framework governing adult content in video games in Indonesia, focusing on the Electronic Information and Transactions Law (Law No. 11/2008) and Ministerial Regulation No. 11/2016. The study finds that game developers can face various penalties, including administrative, criminal, and civil sanctions, if their games contain adult content that violates legal standards. The research underscores the necessity for laws that adapt to technological advancements and regional differences, ensuring that regulations effectively safeguard youth from inappropriate content.